Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.

What to Measure in Aneurysmal Subarachnoid Haemorrhage Research—An International Delphi Survey - Christopher R. Andersen; Justin Presseau; Bev Shea; Maria Luisa Marti; Madeline McCoy; Gordon Fernie; Lauralyn McIntyre; Anthony Delaney; Michaël Chassé; Victoria Saigle; Shawn Marshall; Dean A. Fergusson; et al. (Translational Stroke Research, 2025)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

Number of COVID-19 cases required in a population to detect SARS-CoV-2 RNA in wastewater in the province of Alberta, Canada: Sensitivity assessment - Qiaozhi Li; Bonita E. Lee; Tiejun Gao; Yuanyuan Qiu; Erik Ellehoj; Jiaao Yu; Mathew Diggle; Graham Tipples; Rasha Maal-Bared; Deena Hinshaw; Christopher Sikora; Nicholas J. Ashbolt; et al. (Journal of Environmental Sciences, 2023)

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Quantifying the effects of hydrological changes on long-term water quality trends in temperate reservoirs: insights from a multi-scale, paleolimnological study - Leanne Elchyshyn; Jean-Olivier Goyette; Émilie Saulnier-Talbot; Roxane Maranger; Christian Nozais; Christopher T. Solomon; Irene Gregory-Eaves (Journal of Paleolimnology, 2018)

Cardiorespiratory and perceptual responses to self-regulated and imposed submaximal arm–leg ergometry - Mathew Hill; Christopher Talbot; Michael Puddiford; Michael Price (European Journal of Applied Physiology, 2018)

Inclined transpression in the Neka Valley, eastern Alborz, Iran - Seyed Tohid Nabavi; Manuel Díaz-Azpiroz; Christopher J. Talbot (International Journal of Earth Sciences, 2017)

Mapping of the Asian longhorned beetle’s time to maturity and risk to invasion at contiguous United States extent - Alexander P. Kappel; R. Talbot Trotter; Melody A. Keena; John Rogan; Christopher A. Williams (Biological Invasions, 2017)

Organic matter quantity and source affects microbial community structure and function following volcanic eruption on K asatochi I sland, A laska - Lydia H. Zeglin; Bronwen Wang; Christopher Waythomas; Frederick Rainey; Sandra L. Talbot (Environmental Microbiology, 2016)
Summary In A ugust 2008, K asatochi volcano erupted and buried a small island in pyroclastic deposits and fine ash; since then, microbes, plants and birds have begun to re‐colonize the initially sterile surface. Five years post‐eruption, bacterial 16S r RNA gene and fungal internal transcribed spacer (ITS) copy numbers and extracellular enzyme activity ( EEA ) potentials were one to two orders of magnitude greater in pyroclastic materials with organic matter ( OM ) inputs relative to those without, despite minimal accumulation of OM ( C ). When normalized by OM levels, post‐eruptive surfaces with OM inputs had the highest β‐glucosidase, phosphatase, NAGase and cellobiohydrolase activities, and had microbial population sizes approaching those in reference soils. In contrast, the strongest factor determining bacterial community composition was the dominance of plants versus birds as OM input vectors. Although soil pH ranged from 3.9 to 7.0, and % C ranged 100×, differentiation between plant‐ and bird‐associated microbial communities suggested that cell dispersal or nutrient availability are more likely drivers of assembly than pH or OM content. This study exemplifies the complex relationship between microbial cell dispersal, soil geochemistry, and microbial structure and function; and illustrates the potential for soil microbiota to be resilient to disturbance.

The effects of acute arm crank ergometry and cycle ergometry on postural sway and attentional demands during quiet bipedal standing - Mathew Hill; Christopher Pereira; Chris Talbot; Sam Oxford; Mike Price (Experimental Brain Research, 2015)

Corneal microprojections in coleoid cephalopods - Christopher Talbot; Thomas M. Jordan; Nicholas W. Roberts; Shaun P. Collin; N. Justin Marshall; Shelby E. Temple (Journal of Comparative Physiology A, 2012)

Implications of channel flow analogue models for extrusion of the Higher Himalayan Shear Zone with special reference to the out-of-sequence thrusting - Soumyajit Mukherjee; Hemin A. Koyi; Christopher J. Talbot (International Journal of Earth Sciences, 2012)

Sources for sedimentary bacteriohopanepolyols as revealed by 16S rDNA stratigraphy - Marco J. L. Coolen; Helen M. Talbot; Ben A. Abbas; Christopher Ward; Stefan Schouten; John K. Volkman; Jaap S. Sinninghe Damsté (Environmental Microbiology, 2008)
Summary Bacteriohopanoids are widespread lipid biomarkers in the sedimentary record. Many aerobic and anaerobic bacteria are potential sources of these lipids which sometimes complicates the use of these biomarkers as proxies for ecological and environmental changes. Therefore, we applied preserved 16S ribosomal RNA genes to identify likely Holocene biological sources of bacteriohopanepolyols (BHPs) in the sulfidic sediments of the permanently stratified postglacial Ace Lake, Antarctica. A suite of intact BHPs were identified, which revealed a variety of structural forms whose composition differed through the sediment core reflecting changes in bacterial populations induced by large changes in lake salinity. Stable isotopic compositions of the hopanols formed from periodic acid‐cleaved BHPs, showed that some were substantially depleted in 13 C, indicative of their methanotrophic origin. Using sensitive molecular tools, we found that Type I and II methanotrophic bacteria (respectively Methylomonas and Methylocystis ) were unique to the oldest lacustrine sediments (> 9400 years BP), but quantification of fossil DNA revealed that the Type I methanotrophs, including methanotrophs related to methanotrophic gill symbionts of deep‐sea cold‐seep mussels, were the main precursors of the 35‐amino BHPs (i.e. aminopentol, ‐tetrol and ‐triols). After isolation of the lake ∼3000 years ago, one Type I methanotroph of the ‘methanotrophic gill symbionts cluster’ remained the most obvious source of aminotetrol and ‐triol. We, furthermore, identified a Synechococcus phylotype related to pelagic freshwater strains in the oldest lacustrine sediments as a putative source of 2‐methylbacteriohopanetetrol (2‐Me BHT). This combined application of advanced geochemical and paleogenomical tools further refined our knowledge about Holocene biogeochemical processes in Ace Lake.

QTL analyses of lineage-negative mouse bone marrow cells labeled with Sca-1 and c-Kit - Mays Jawad; Clare Cole; Abigail Zanker; George Giotopoulos; Simon Fitch; Christopher J. Talbot; Mark Plumb (Mammalian Genome, 2008)

Photochemistry in the Arctic Free Troposphere: Ozone Budget and Its Dependence on Nitrogen Oxides and the Production Rate of Free Radicals - Craig Stroud; Sasha Madronich; Elliot Atlas; Christopher Cantrell; Alan Fried; Brian Wert; Brian Ridley; Fred Eisele; Lee Mauldin; Richard Shetter; Barry Lefer; Frank Flocke; et al. (Journal of Atmospheric Chemistry, 2004)

A strategy for the integration of QTL, gene expression, and sequence analyses - Robert Hitzemann; Barry Malmanger; Cheryl Reed; Maureen Lawler; Barbara Hitzemann; Shannon Coulombe; Kari Buck; Brooks Rademacher; Nicole Walter; Yekatrina Polyakov; James Sikela; Brenda Gensler; et al. (Mammalian Genome, 2003)

Fine scale mapping of a genetic locus for conditioned fear - Christopher J. Talbot; Richard A. Radcliffe; Jan Fullerton; Robert Hitzemann; Jeanne M. Wehner; Jonathan Flint (Mammalian Genome, 2003)